GERAKAN SOSIAL KELOMPOK PEREMPUAN PEJUANG SERIBANDUNG (KPPS) DALAM KONFLIK TENURIAL DI OGAN ILIR - Yui Zahana; Dadang Hikmah Purnama; Diana Dewi Sartika (Jurnal Analisa Sosiologi, 2024)
The Seribandung Women Fighters Group is a grassroots women's group that carries out a social movement to fight for community land which has been controlled for forty-two years by a state-owned company, PT Perkebunan Nusantara VII Cinta Manis. This research aims to analyze the meaning of the social movement carried out by KPPS, especially since this conflict has been very long and has not yet been resolved. The method used in this research is qualitative with Alfred Schutz's phenomenological approach. The results of this study found that the experience, knowledge, awareness and motives of KPPS shape the meaning of social movements that have been carried out. KPPS has experience doing social movements from demonstrations to new social movements, namely campaigns through MSME products. This experience shapes KPPS knowledge in conducting social movements in the form of dialogue, advocacy, campaigning and organizing strategies. They get this knowledge because of continuous experience. This activity forms KPPS awareness to continue to carry out social movements supported by the land return motive. KPPS believes that farming is a hereditary legacy from ancestors and land is a source of livelihood for the community so that land conversion carried out by companies has an impact on the absence of productive land, changing the type of work of women from farmers to farm laborers, the high criminalization carried out by the authorities to the shrinking of village administrative areas. This is the basis of the social movement carried out by KPPS to this day. KPPS itself interprets land as a source of life, human life and death depend on land and the seizure of land rights by companies is a violation of human rights.